BAG3 regulates contractility and Ca2 + homeostasis in adult mouse ventricular myocytes. (March 2016) - Feldman, Arthur M.; Gordon, Jennifer; Wang, JuFang; Song, Jianliang; Zhang, Xue-Qian; Myers, Valerie D.; Tilley, Douglas G.; Gao, Erhe; Hoffman, Nicholas E.; Tomar, Dhanendra; Madesh, Muniswamy; Rabinowitz, Joseph; et al.
Abstract: Bcl2-associated athanogene 3 (BAG3) is a 575 amino acid anti-apoptotic protein that is constitutively expressed in the heart. BAG3 mutations, including mutations leading to loss of protein, are associated with familial cardiomyopathy. Furthermore, BAG3 levels have been found to be reduced in end-stage non-familial failing myocardium. In contrast to neonatal myocytes in which BAG3 is found in the cytoplasm and involved in protein quality control and apoptosis, in adult mouse left ventricular (LV) myocytes BAG3 co-localized with Na + –K + –ATPase and L-type Ca 2 + channels in the sarcolemma and t-tubules. BAG3 co-immunoprecipitated with β1-adrenergic receptor, L-type Ca 2 + channels and phospholemman. To simulate decreased BAG3 protein levels observed in human heart failure, we targeted BAG3 by shRNA (shBAG3) in adult LV myocytes. Reducing BAG3 by 55% resulted in reduced contraction and [Ca 2 + ]i transient amplitudes in LV myocytes stimulated with isoproterenol. L-type Ca 2 + current (ICa ) and sarcoplasmic reticulum (SR) Ca 2 + content but not Na + /Ca 2 + exchange current (INaCa ) or SR Ca 2 + uptake were reduced in isoproterenol-treated shBAG3 myocytes. Forskolin or dibutyryl cAMP restored ICa amplitude in shBAG3 myocytes to that observed in WT myocytes, consistent with BAG3 having effects upstream and at the level of the receptor. Resting membrane potential and action potential amplitude were unaffected but APD50 and APD90 were prolonged in shBAG3 myocytes. Protein levels of Ca 2 + entry molecules and other important excitation–contraction proteins were unchanged in myocytes with lower BAG3. Our findings that BAG3 is localized at the sarcolemma and t-tubules while modulating myocyte contraction and action potential duration through specific interaction with the β1-adrenergic receptor and L-type Ca 2 + channel provide novel insight into the role of BAG3 in cardiomyopathies and increased arrhythmia risks in heart failure. Highlights: Bcl2-associated athanogene 3(BAG3) is reduced in heart failure. BAG3 is expressed on the sarcolemma and t-tubules of adult cardiac myocytes. BAG3 associates with β1 adrenergic receptor, L-type Ca 2 + channel and phospholemman. BAG3 reduction decreases contraction and [Ca 2 + ]i transient amplitudes in adult myocytes stimulated with isoproterenol. BAG3 downregulation reduces L-type Ca 2 + current and prolongs action potential.